The Effect of Student Team Achievement (STAD) Cooperative Learning Model on the Fourth-Grade Students’ Learning Outcomes at Assisi Medan Elementary School - Saskia Kristina; Bogor Lumbanraja1; Patri Janson Silaban; Rumiris Lumban Gaol; Juliana (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the effect of applying the Student Team Achievement Division (STAD) cooperative learning model on student learning outcomes on the theme The Area Where I Live in Grade IV at SD Assisi Medan during the 2022/2023 academic year. The study employs a quantitative research approach. The research population consists of 180 fourth-grade students at SD Assisi Medan, while the sampling technique used is simple random sampling, resulting in a sample of 44 fourth-grade students. The findings indicate that students’ learning outcomes through the application of the Student Team Achievement Division (STAD) cooperative learning model fall into the very good category, with an average score of 83.48. The correlation test yields a value of 0.958, indicating that rcount (0.958) ≥ rtable (0.297), thus confirming that Ha is accepted. This demonstrates a significant effect of the Student Team Achievement Division (STAD) cooperative learning model on students’ learning outcomes. Furthermore, the t-test results show that tcount = 21.720 ≥ ttable = 2.015, which further supports the acceptance of Ha. These results indicate a significant positive effect of the Student Team Achievement Division (STAD) cooperative learning model on students’ learning outcomes on the theme The Area Where I Live in Grade IV at SD Assisi Medan during the 2022/2023 academic year.